PROSPEK DAN STRATEGI PERDAGANGAN TERNAK KAMBING DALAM MEREBUT PELUANG PASAR DUNIA - Rusdiana, S.; Praharani, L.; Adiati, dan U. (Agriekonomika, 2014)
ABSTRAKProspek kambing cukup berpeluang untuk merebut pasar ekspor menjelang era perdagangan bebas. Hal ini dikarenakan semua negara membuka pasar bagi masuknya produk impor minimal 5% dari konsumsi yang dibutuhkan. Produk dalam negeri dituntut mampu bersaing dengan produk impor baik dari segi kualitas, kuantitas dan kontinuitasnya. Jenis ternak dan produk kambing / domba mulai dikembangkan untuk memenuhi permintaan pasar.Berdasarkan peluang perdagangan pasar global, kambing merupakan komoditas unggulan untuk dipacu perkembangan populasi, sebagai ternak ekspor. Berdasarkan permasalahan tersebut maka, tujuan tulisan ini adalah untuk mengulas beberapa prospek dan strategi perdagangan ternak kambing dalam upaya merebut peluang pasar duniayang menguntungkan bagi pendapatan devisa negara. Jenis impor ternak sapi, kambing dan domba dalam kurun waktu 2008-2012, namun secara umum terjadi kenaikan pada impor sapi hidup. Impor daging sapi cenderung menurun, impor kambing/domba hidup dan daging cenderung stabil.Keadaan tersebut mengindikasikan defisit dalam negeri meningkat. Guna mengatasi hal ini maka perlu ada wacana yang bersifat horisontal di perdagangan pasar dunia, dimana pasar tidak memonopili terhadap produk ekspor. Demikian pula diperlukan kerjasama ekonomi Sub-Regional, segitiga pertumbuhan (Growth Triangle) atau wilayah pertumbuhan (Growth Area), yang saling berketerkaitan (lingkage) ekonomi antar daerah.Kata Kunci : prospek,strategi, perdagangan, kambing, expor ABSTRACTThe prospectis quitelikely tobe able toseize the go a tex port markets, the seconditions before the era offree trade open markets of all countries for the entry ofimported products at a minimum of 5% of the required consumption, consumers determine alternative choices like meat products imported or local meat products. Domestic product sare required to compete with imported products in terms of quality, quantity and continuity, live stock and products go at and sheep began to be developed to meet the market demand, the development of go at should receiveserious attention, goat productsin the open market, domestic and export market sacceptable, in linewith the changingpolitical landscape inIndonesia, whichled to theera ofVdemocratization and globalization. Based on the world market trading opportunities of globalizati on goat is excellent commodity to be driven population growth, a sex ports of live stock, Based on the problems stretcher purpose of this paper is to mengkulas some prospects and goat strading strategies in an attempt to seize the opportunities the world market, global export, as the business economy favorable to the States foreign exchange earnings, especially for the people of Indonesia. Type imported cattle, goat sand sheep in the period 2008-2012, in general there is an increase in imports of live cattle, beef import sare likely to decline, imports of goat/sheep meattend to live and stable, indicating a deficit situationin the country increased. Weaknessis considereda common thing in every developed country, the necessary discourse bersipathorisentalin Duni market trading the market does not memonopili to export products, required Sub-Regional economic cooperation, also known as the triangle of growth (Growth Trangle) orregional growth (Growth Area), is a form ofinterdependence, in collaboration (lingkage) inter-regional economy.Keywords: prospects, strategies, trading, goats, export